Electrochemically generated bimetallic reductive mediator Cu1+ [Ni2+ (CN) 4] 1− for the degradation of CF4 to ethanol by electro-scrubbing - Muthuraman, G.; Ramu, A. G.; Cho, Y-H; McAdam, Ewan J.; Moon, Ilshik S. (SAGE, 2018)
Remediation of electronic gas CF4 using commercially available technologies results in another kind of greenhouse gas and corrosive side products. This investigation aimed to develop CF4 removal at room temperature with formation of useful product by attempting an electrogenerated Cu1+[Ni2+(CN)4]1− mediator. The initial electrolysis of the bimetallic complex at the anodized Ti cathode demonstrated Cu1+[Ni2+(CN)4]1− formation, which was confirmed by additional electron spin resonance results. The degradation of CF4 followed mediated electrochemical reduction by electrogenerated Cu1+[Ni2+(CN)4]1−. The removal efficiency of CF4 of 95% was achieved by this electroscrubbing process at room temperature. The spectral results of online and offline Fourier transform infrared analyzer, either in gas or in solution phase, demonstrated that the product formed during the removal of CF4 by electrogenerated Cu1+[Ni2+(CN)4]1− by electroscrubbing was ethanol (CH3CH2OH), with a small amount of trifluoroethane (CF3CH3) intermediate.
Keywords: Bimetallic mediator; Cu1+[Ni2+(CN)4]1−; MER; CF4 degradation; ethanol formation